2002
DOI: 10.1287/mnsc.48.1.138.14274
|View full text |Cite
|
Sign up to set email alerts
|

Commercializing Knowledge: University Science, Knowledge Capture, and Firm Performance in Biotechnology

Abstract: Commercializing knowledge involves transfer from discovering scientists to those who will develop it commercially. New codes and formulae describing discoveries develop slowly -with little incentive if value is low and many competing opportunities if high. Hence new knowledge remains naturally excludable and appropriable. Team production allows more knowledge capture of tacit, complex discoveries by firm scientists. A robust indicator of a firm's tacit knowledge capture (and strong predictor of its success) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
458
2
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(489 citation statements)
references
References 22 publications
11
458
2
18
Order By: Relevance
“…A much-cited study by Van Looy and colleagues (2004) suggests that researchers who engage in entrepreneurial activities also have increased publication output. A similar trend was observed earlier in the seminal work by Zucker, Darby, and co-authors who showed that, in the field of biotechnology, top scientists are both leaders in publications and commercialization (Zucker & Darby, 2005;Zucker et al, 1998;Darby & Zucker, 2003;Zucker et al, 1998Zucker et al, , 2002. To the extent that products and services based on biotechnology have made positive contributions to society, for example through the development of new medicines or environmental applications, the commercialization of research results can be considered a critical component to the achievement of public health outcomes.…”
Section: Commercialization As the Critical Component To Creating Socisupporting
confidence: 78%
See 1 more Smart Citation
“…A much-cited study by Van Looy and colleagues (2004) suggests that researchers who engage in entrepreneurial activities also have increased publication output. A similar trend was observed earlier in the seminal work by Zucker, Darby, and co-authors who showed that, in the field of biotechnology, top scientists are both leaders in publications and commercialization (Zucker & Darby, 2005;Zucker et al, 1998;Darby & Zucker, 2003;Zucker et al, 1998Zucker et al, , 2002. To the extent that products and services based on biotechnology have made positive contributions to society, for example through the development of new medicines or environmental applications, the commercialization of research results can be considered a critical component to the achievement of public health outcomes.…”
Section: Commercialization As the Critical Component To Creating Socisupporting
confidence: 78%
“…Scientists who patent more seem to also publish more (Buenstorf, 2009;Van Looy et al, 2004;Zucker et al, 2002), and researchers engaged in commercialization activities seem to maintain appreciation for open science (Shibayama, 2012), even though the open dissemination of results may be slowed down (Perkmann et al, 2013).…”
Section: Commercialization As Complementary To Social Benefitsmentioning
confidence: 99%
“…University spinoffs tend to be located in close proximity to their origin university, and, as such, contribute to their local economy (Feldman 1999;Zucker et al 2002;Breznitz and Anderson 2006).…”
Section: Knowledge Transfermentioning
confidence: 99%
“…Engineers in industrial R&D were found to source considerable scientific knowledge and idea for solving technological problems through social relationships with scientists (Gibbons and Johnston 1974;DeBresson and Amesse 1991;Vedovello 1997;DeCarolis and Deeds 1999;Simeth and Raffo 2013). To take benefit of knowledge spillover through informal communications, industrial organizations are actively building relationships with scientific institutes, e.g., industry-academic joint research or other collaborations such as the sharing of equipment to foster conditions for their engineers to work together with experts in science (Anselin et al 1997;Vedovello 1997;Zucker et al 2002;Cassiman et al 2008). Personal contacts with scientists can provide information about theories and principles to help solve technological problems by transforming scientific literature into readily understandable language for engineers (Gittelman and Kogut 2003).…”
Section: Regional Scientific Knowledge Spillovermentioning
confidence: 99%